PENGUATAN PRODUKSI BUDIDAYA SAWAH TAMBAK MELALUI PENINGKATAN PAKAN ALAMI DENGAN PEMANFAATAN SUMBER DAYA LOKAL DI DESA BABATAGUNG KECAMATAN DEKET KABUPATEN LAMONGAN - Lutfiyah, Lailatul; Sulmartiwi, Laksmi; Nirmala, Dwitha; Satyantini, Woro Hastuti (Jurnal Abdi Insani, 2025)
Rice pond cultivation is an effort to maintain fish in rice fields before planting rice and after the rice is harvested, the type of pond paddy field cultivation in Lamongan Regency uses a rotating rotation type that has a time interval for fish maintenance during the rainy season (Sequential/Alternate farming). Liquid organic fertilizer is a type of fertilizer derived from the fermentation of organic matter. The fermentation of these organic materials can produce more than one nutrient. The use of organic waste such as rice straw, water hyacinth, and fish offal can be used as an alternative source of nutrients that can be used to make liquid organic fertilizer. The expected target of this activity is training in the use of local resources to overcome the termination of inorganic fertilizer subsidies. Prolonged use of inorganic fertilizers will have an impact on the environment because it can result in nutrient imbalances. An alternative that can be done is the application of organic fertilizer to continue to increase the productivity of rice pond cultivation in Lamongan Regency. The manufacture of organic fertilizer can utilize local natural resources including rice straw, water hyacinth and fish offal which can be used as Liquid Organic Fertilizer ingredients. Making probiotics and composted cow dung as organic fertilizer to increase natural feed production. This activity was attended by 50 participants consisting of farmer groups from Babatagung Village, Deket District, Lamongan Regency. Before and after the training, questionnaires were filled out to the trainees for activity evaluation materials. Based on the questionnaire that has been distributed, 98% of fish farmers have known about making organic fertilizers from local resources. As many as 94% of farmers are interested in applying organic fertilizer to fish farming ponds and 70% of farmers are interested in increasing their income through the sale of locally-based organic fertilizers. In addition, farmers are also provided with how to maintain and measure water quality in fish farming ponds. After the training on making Liquid organic fertilizer, Liquid organic fertilizer was applied to denfarm ponds to determine the advantages of POC application.